Association of CYP2C9∗3 and CYP2C8∗3 Non-Functional Alleles with Ibuprofen-Induced Upper Gastrointestinal Toxicity in a Saudi Patient - Amina M. Bagher (Case Reports in Medicine)
Ibuprofen is a non-steroidal anti-inflammatory drug (NSAID) widely used to alleviate pain and inflammation. Although it is generally considered safe, common adverse drug reactions of ibuprofen include stomach pain, nausea, and heartburn. It can also cause gastrointestinal (GI) bleeding, especially in individuals with a history of GI ulcers or bleeding disorders. Ibuprofen is predominantly metabolized by the cytochrome P450 (CYP) enzymes CYP2C9 and CYP2C8. Individuals carrying the CYP2C9∗3 or CYP2C8∗3 non-functional alleles have reduced enzyme activities resulting in elevated ibuprofen plasma concentrations and half-life. We presented a case of a 31-year-old Saudi female patient with a history of rheumatoid arthritis (RA) who had taken ibuprofen at 600 mg twice daily for eight weeks. The patient presented to the emergency department with symptoms including nausea, vomiting, severe abdominal pain, and black tarry stools. An emergency esophagogastroduodenoscopy was performed on the patient, which revealed a deep bleeding ulcer measuring 1 × 1 cm in the antrum of the stomach. Laboratory investigations indicated anemia (hemoglobin: 7.21 g/dL and hematocrit: 22.40 g/dl). The patient received intravenous proton pump inhibitors and a packed red blood cell transfusion. Genetic analysis revealed that the patient was a carrier of CYP2C9∗3 and CYP2C8∗3 variant alleles, indicating that the patient is a poor metabolizer for both enzymes. The patient’s symptoms improved over the subsequent days, and she was discharged with instructions to avoid NSAIDs. This is the first reported Saudi patient homozygous for CYP2C9∗3 and CYP2C8∗3 variant alleles, which led to ibuprofen-induced upper GI toxicity. This case demonstrates the importance of contemplating CYP2C9 and CYP2C8 genetic variations when administrating NSAIDs like ibuprofen. Careful assessment of the risks and benefits of NSAID therapy in each patient and consideration of alternative pain management strategies must be conducted when appropriate.